Cardiovascular abnormalities already occurred in newly-diagnosed patients with early-onset type 2 diabetes - Hong Lian; Qian Ren; Wei Liu; Rui Zhang; Xiantong Zou; Simin Zhang; Yingying Luo; Wei Deng; Qiuping Wang; Lin Qi; Yufeng Li; Wenbo Wang; et al. (Cardiovascular Diabetology)
Abstract Background The prevalence of early-onset type 2 diabetes (EOD) is rapidly increasing. This study intends to screen for early cardiovascular abnormalities in patients newly diagnosed with EOD and evaluate the cardiovascular risk across cluster phenotypes. Method A total of 400 patients ≤ 40 years old with newly diagnosed type 2 diabetes were enrolled from the START cohort (the Study of The newly diAgnosed eaRly onset diabeTes). Cluster classification was performed using the K-means method based on age, BMI, HbA1c, HOMA2-β, HOMA2-IR, and GAD antibodies. Echocardiography and carotid ultrasound were performed within 3 months of diabetes diagnosis. Carotid ultrasound abnormalities included intimal thickening and plaque formation, while echocardiography assessed changes in cardiac structure and systolic/diastolic function. Cluster-specific partitioned polygenic scores (pPS) were used to validate our findings from a genetic perspective. Result Carotid artery abnormalities were detected in 26.3% of patients, and echocardiography abnormalities were observed in 20.0%. Patients with severe insulin resistant diabetes (SIRD) had the highest incidence of carotid artery abnormality (40.0%). After adjusting for relevant risk factors, fasting C-peptide levels were significantly associated with a 1.247-fold increase in the risk of carotid artery abnormalities. Left atrial enlargement was more prevalent in the SIRD (16.7%) and mild obesity-related diabetes (MOD) (18.5%) classifications. A high proportion of patients with SIRD had abnormal left ventricular geometry (36.1%). Increases in BMI, fasting C-peptide level and HOMA2IR were accompanied by a further increase in left atrial enlargement risk by 1.136-, 1.781- and 1.687-fold respectively. The pPS for lipodystrophy was higher in the EOD group with plaque formation, and showed a significant linear correlation with the ratio of the left atrial anteroposterior diameter to body surface area (LAAP/BSA) (R = 0.344, p < 0.001). Conclusion Heart and carotid artery abnormalities are common in patients with early-onset T2DM at the time of diagnosis. Patients with obesity and insulin resistance are at higher risk for cardiovascular abnormalities. Cluster classification based on clinical characteristics enables more accurate identification of patients at increased risk of cardiovascular complications at an early stage. Graphical abstract